A new experimental model of intrinsic denervation in ileum from wistar rats through intramural microinjections of benzalkonium chloride1 - Ribeiro, Juliana O. [UNESP]; Ferreira, Marília G.P.A. [UNESP]; Marques, Isabela C.S.; Alvarenga, Carolina; Nardi, Andrigo B. [UNESP]; Garcia, Sérgio B.; Montanhim, Gabriel Luiz [UNESP]; Moraes, Paola C. [UNESP] (FapUNIFESP (SciELO), 2019)
Extensive literature is available about the intrinsic denervation of segments of the digestive tube through the application of CB in the serosa of the viscera. However, this technique has some disadvantages like causing peritonitis, flanges and high mortality, limiting its use in humans. The aim of the present study was to evaluate the feasibility of benzalkonium chloride (CB) to induce intrinsic chemical denervation, through applications of CB in the intramural ileum of wistar rats, as well as deepen the knowledge about the evolution of neuronal injury caused in the process. We used 40 rats, divided into two groups (control-GC and benzalkonium-GB) of 20 animals each, divided into four sub-groups according to the time of postoperative assessment of 24, 48 hours, 30 and 90 days. The animals were submitted to intramural microinjections of sterile saline solution 0.9% (GC) or benzalkonium chloride (GB) in ileal portion, and subsequent histopathological analysis and immunohistochemistry for evaluation of neuronal injury. A significant decrease (p<0.05) was found of the neuronal myenteric count over time in groups, GB3, GB4 and GB2. The specific positive immunolabeling for H2AX and Caspase-3 confirmed the results obtained in the histopathological evaluation, denoting the ignition of irreversible cell injury in 24 hours, evolving into neuronal apoptosis in 48 hours after application of the CB 0.3%. Under the conditions in which this work was conducted, it can be concluded that the application of CB 0.3% by means of microinjections intramural in the ileal wall is able to induce intrinsic chemical denervation of the diverticulum of wistar rats and that the main mechanism of neuronal death is induction of apoptosis.
Um novo modelo experimental de desnervação intrínseca em íleo de ratos wistar através de micro injeções intramurais de cloreto de benzalcônio.